The Role of Complementary Currencies in Enhancing Social and Economic Welfare: The Case of Afghanistan - Ahmadi, Ahmad Naqib; Laallam, Abdelkader; Kashi, Aghilasse; Fathelbab, Osama Elsayed Abdelmaksoud (Journal of Ecohumanism, 2024)
Complementary currencies are alternative units of exchange designed to complement official currencies. They have been used in both developed and developing countries to bridge societal and economic gaps that are inadequately addressed by official monetary systems. This paper explores the potential for Afghanistan to implement complementary currencies and the challenges it may face in this process. A qualitative research approach is employed, using analogical methods and content analysis to assess the potential advantages that complementary currencies could offer Afghanistan. The findings suggest that complementary currencies could significantly contribute to Afghanistan’s economic and social welfare, particularly in addressing gaps in resource distribution. The paper emphasizes critical success factors for the introduction of complementary currencies in Afghanistan, notably the need for political will, government support, legal frameworks, public awareness, and international cooperation. This study is the first to address the potential for complementary currencies in Afghanistan, highlighting its importance and forecasting its contribution to enhancing the financial system in the country.